Genetic diversity analyzed by quantitative traits among rice (Oryza sativa L.) genotypes resistant to blast disease - Latif, Mohammad Abdul; Rahman, Md. Mukhlesur; Kabir, Md. Shahjahan; Ali, M. A.; Islam, Md. Touhidul; Yusop, Mohd Rafii (Academic Journals, 2011)
Genetic diversity was studied for blast resistant and susceptible genotypes using 13 morphological characters. Plant height, days to flowering and maturity, panicle length, number of spikelet per panicle, number of filled grain per panicle, number of unfilled grain per panicle, 1000-grain weight and yield per hill were indicated as important contributors to genetic divergence in 14 rice genotypes. The first 3 principal components accounted for 78.72% of the total variation among resistant and susceptible rice genotypes. The genotypes were grouped into 7 clusters according to Mohalanobis’s D2 statistics and canonical vector analysis. On the basis of cluster distances, high yielding along with highly susceptible genotype, Bangladesh Rice Research Institute (BRRI) dhan29 could be crossed with resistant genotypes, BR 6017-3-3-4-1 and Zong-yu 7. Similarly, BRRI dhan28 could be crossed with Qing Liali No.1 for the development of blast resistant rice varieties with higher yield.